Verifying the Miles and Snow strategy types in Australian small- and medium-size enterprises. (April 2013) - Blackmore, Karen; Nesbitt, Keith
In this paper we set out to verify the existence of Miles and Snow strategy types in Australian small- and medium-size enterprises (SMEs) through objective classification. Australian SMEs, in particular, are interesting as they are reported to have some unique characteristics, with as many as 70% following a low growth or life-style pathway. While numerous empirical studies have been conducted to validate the existence and characteristics of the Miles and Snow strategy types in different domains for both larger and smaller enterprises, these studies typically rely on a subjective, 'self-typing' approach. In this study we employ a more objective approach by identifying measures from existing survey data that capture the strategic dimensions proposed by Miles and Snow. We use these objective measures in a K -means cluster analysis to identify four different strategic groups. Three of the groups correspond to the three 'viable' Miles and Snow strategy types of Defender, Prospector and Analyser; however, we also identify a 'Static' strategy type that constitutes 42% of SMEs in the sample.